Boosting light harvesting and charge separation of WO3via coupling with Cu2O/CuO towards highly efficient tandem photoanodes. Issue 22 (12th April 2021) - Khalifa, Mahmoud A.; Shen, Luying; Zheng, Jianming; Xu, Chunye
Abstract : A highly efficient photoanode with a tandem structure of ITO/WO3 /Cu2 O/CuO produces a photocurrent about 1.4 and 5.5 times the measured values for ITO/WO3 /Cu2 O and ITO/WO3 ones, respectively. Abstract : Photoanodes based on semiconductor WO3 have been attractive due to its good electron mobility, long hole-diffusion length, and suitable valence band potential for water oxidation. However, the semiconductor displays disadvantages including a relatively wide bandgap, poor charge separation and transfer, and quick electron–hole recombination at the interface with the electrolyte. Here we present a significantly improved photoanode with a tandem structure of ITO/WO3 /Cu2 O/CuO, which is prepared first by hydrothermally growing a layer of WO3 on the ITO surface, then by electrodepositing an additional layer of Cu2 O, and finally by heat-treating in the air to form an exterior layer of CuO. Photocurrent measurements reveal that the prepared photoanode produces a maximum current density of 4.7 mA cm −2, which is, in comparison, about 1.4 and 5.5 times the measured values for ITO/WO3 /Cu2 O and ITO/WO3 ones, respectively. These enhancements are attributed to (1) harvested UV, visible, and NIR light of the solar spectrum, (2) accelerated charge separation at the heterojunction between WO3 and Cu2 O/CuO, (3) better electrocatalytic activity of formed Cu x O than pure Cu2 O, (4) formation of a protective layer of CuO. This study thus may lead to a promising way to make high-performance and low-cost photoanodes for solar energy harvesting.